false
Small Joy Sue

Budget: $15

Solved!

dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2 dy/dx=4t/(2yt^2+2t^2+y+1) a) find the general solution. ok if left as implicit b) find a solution that satisfies the condition y(0)=2

Answer

Small Tutor Jack Kim

{ y'(t) = 4t/(2y(t)t² + 2t² + y(t) + 1) { y(0) = 2 Rewrite your equation y'...